Piezoresistive response of carbon nanotubes-polyamides composites processed by extrusion - Arboleda, L. (2013)
The piezoresistive response of carbon nanotube (CNT)-polyamide composites processed by extrusion has been investigated as a function of CNT amount, polyamide 66 (PA66) / polyamide 6 (PA6) ratio, within the matrix and the masterbatch used to incorporate the CNT into the composite (PA66 masterbatch or PA6 masterbatch). The dispersion level of CNT in PA66/PA6 matrix was evaluated and related with the thermal, electrical and electromechanical properties. It is concluded that the inclusion of the CNT in the PA6 masterbatch helps to improve dispersion leading to larger values of the electrical conductivity in the composites prepared with larger PA66 content. On the other hand, the Gauge Factor (GF), which provides the sensitivity of a piezoresistive sensor, is larger for composites prepared from the PA66 masterbatch. The increase of PA66 content improving also the electromechanical response and GF reaches values up to 6. This fact demonstrates the suitability of the materials for sensor applications produced in an up-scaled production way.